PENGARUH MANAJEMEN KESISWAAN TERHADAP PEMBENTUKAN KARAKTER KEDISIPLINAN SISWA - Bayu ma’ruf qoustaulani; Umiarso Umiarso; Muhammad Yusuf (PAI RAFAH, 2023)
Student management in schools has a significant role in shaping student character and discipline. One important aspect of student management is student leadership. Student leadership includes various activities that involve students in organizing and managing school activities, such as student organizations, extracurricular activities, and other self-development programs. Student leadership can be a determining factor in shaping student character, especially in terms of discipline. This study aims to evaluate the influence of student leadership on student character building in terms of discipline. Quantitative analysis method was used in this study. The research group consisted of 128 students in grades VII, VIII, and IX of SMP Muhammadiyah 1 Malang City. The research sample of 94 respondents was obtained through simple random sampling. Data were collected through observation, questionnaire, and documentation. The survey data were processed using Likert scale. Classical acceptability tests such as normality test, homogeneity test, and linearity test were conducted using SPSS for Windows Version 21 program during data analysis. The results of the discussion show that student leadership has a positive effect on the formation of student character discipline at SMP Muhammadiyah 1 Malang City. Thus, student leadership has an impact on the formation of student character in accordance with discipline. These results have implications for the theories underlying the research variables and highlight the importance of applying student leadership concepts that are in line with existing theories to achieve optimal student discipline.